2018
DOI: 10.1038/s41419-018-1046-3
|View full text |Cite
|
Sign up to set email alerts
|

The antipsychotic agent trifluoperazine hydrochloride suppresses triple-negative breast cancer tumor growth and brain metastasis by inducing G0/G1 arrest and apoptosis

Abstract: Women with aggressive triple-negative breast cancer (TNBC) are at high risk of brain metastasis, which has no effective therapeutic option partially due to the poor penetration of drugs across the blood−brain barrier. Trifluoperazine (TFP) is an approved antipsychotic drug with good bioavailability in brain and had shown anticancer effect in several types of cancer. It drives us to investigate its activities to suppress TNBC, especially the brain metastasis. In this study, we chose three TNBC cell lines MDA-MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…In fact, TFP also interferes with the invasive growth of multiple human cell types derived from lung and breast cancer, hepatocellular carcinoma, or T‐cell lymphoma. TFP offers a limited cytotoxic profile and is therefore discussed as potential available drug in cancer therapy (Feng et al , ; Pulkoski‐Gross et al , ). In glioblastoma, TFP suppresses tumor cell proliferation and invasion in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TFP also interferes with the invasive growth of multiple human cell types derived from lung and breast cancer, hepatocellular carcinoma, or T‐cell lymphoma. TFP offers a limited cytotoxic profile and is therefore discussed as potential available drug in cancer therapy (Feng et al , ; Pulkoski‐Gross et al , ). In glioblastoma, TFP suppresses tumor cell proliferation and invasion in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the upregulation of miR-128 inhibited the expression of cyclin D1 and Rb. Cyclin D1 is a critical protein for the regulation of the G1 phase of the cell cycle, and Rb promotes the transition of cells from G1 to S phase (29). Therefore, these data indicate that a decrease in miR-128 expression under ZD conditions promotes the occurrence of esophageal cancer by regulating cyclin D1 and Rb expression.…”
Section: Discussionmentioning
confidence: 70%
“…However, another therapeutic potential of TFP has been reported. TFP suppressed the growth of tumor and brain metastasis by inducing G0/G1 cell cycle arrest of triple-negative breast cancer (TNBC) without causing detectable side effects in vivo [ 37 ]. TFP, a novel autophagy inhibitor, increases radiosensitivity in glioblastoma by impairing homologous recombination [ 38 ].…”
Section: Discussionmentioning
confidence: 99%